A comunicação das marcas no Facebook : caracteristicas visuais e de interação - Francisco, Ana Rita Felizardo, 1992- (2016)
The following study addresses the key features and purposes of the way brands communicate on Facebook, namely those who concern visual communication, such as profile and cover images, as well as advertisements. This essay is divided in two main sections: in the first part some relevant concepts to the topic under study are framed within a literature review; in the latter section an exploratory study is undertaken based on a sample of six brands from three different sectors. This study aims to provide a an in-depth picture of the main visual attributes of communication, both individually and in comparison between separate brands and industries, and additionally on how much users engage with adverts. The present research suggests that brands are concerned with the visual conveyance of information on Facebook. The amount of audience interaction is particularly low compared to the totality of page followers, reaching its lowest rates on the real estate sector and, on the other hand, peaking on the restaurant industry. This work regards a limited and specific set of brands, and thus the implications from this study can only serve its framework, also being advisable not to extrapolate the results. Nevertheless, the comprehensive gathering of data and its interpretation allows to point out that a cohesive visual image capable of triggering interaction, positive reviews and sharing can be a major investment to a brand